180 Impacts that Cause Transiently Symptomatic Mild Traumatic Brain Injury Can Also Cause Intracranial Tissue Schisis in a Juvenile Rodent Model. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Frim, David M.; Wright, David W.; Bailes, Julian E.
Abstract: INTRODUCTION: Mild traumatic brain injury (mTBI) in helmeted humans from a single concussive head injury is poorly defined regarding both short- and long-term effects as well as potential degree of intracranial injury. We used a helmeted juvenile rodent model of mTBI allowing variable power cranial side-impact in order to study this process. METHODS: A cranial impacter device was created that delivered side impacts up to 12.5 joules to the head of a stationary helmeted rodent. Juvenile rats (100-150 gm) were anesthetized and impacted with variable power, euthanized at variable times after impact, and analyzed for brain injury via immunohistochemistry. RESULTS: At impacts of 2J, 7J, and 12J, rats survived with only brief transient neurological deficit; in rats harvested up to 7d post-injury from 2J to 7J of force, both coup and contra-coup schisis between corpus callosum and subcortical white matter was seen. Neither bleeding nor blood brain barrier disruption were seen in animals harvested beyond 2 days, though it was present around injuries in animals harvested within 6 hours of injury. CONCLUSION: In helmeted animals, impacts within a wide range of power cause white matter schisis injuries without neurological deficit. These lesions can be bilateral. These observations show that in our model, impact strengths that cause experimental mTBI can also cause structural intracranial injuries without neurological deficits.